Algoritmos de inteligência de enxame para otimização binária - Biuk, Lucas Henrique (2019)
This paper brings together a variety of bio-inspired algorithms specialized in solving binary optimization problems. The focus is on swarm intelligence algorithms, such as Particle Swarm Optimization (PSO) and Fish School Search (FSS), with the aim of determining the advantages of each one, comparing their performance for binary tasks. To this end, they are implemented in MATLAB [marca registrada] software, in order to facilitate the statistical analysis of the results obtained by simulating problems with various dimensions, such as One Max Problem and Knapsack Problem. The computational results, partially compared with evolutionary computation techniques, reveal that the PSO is able to reach the best overall performances, followed by the improved version of the binary FSS.